Louvor ao embranquecimento? Uma análise da pintura A Redenção de Cam (1895) por suas historicidades - Reis, Miguel Lucio dos (2022)
The general objective of this dissertation is the analysis of the work The Redemption of Cham, painting presented in 1895 by the Galician artist and teacher naturalized Brazilian, Modesto Brocos (1852-1936). From some reading keys, such as sacredness, feminine, science and social race, the picture was problematized in order to understand it by its potentialities and through its historical aspects. How and which routes were used in the composition of the tropicalized and progressively whiter family in 1895? Split into three chapters, which somehow gather our interpretation matrices, the research specifically discusses: the figure and the relation of Modesto Brocos in the production of the canvas, the links that the image establishes between christianity and scientific theories at the end of the 19th Century and, finally, the pictorial network of which painting is part, in order to establish dialogues and ways of translating something from the visual field. Each chapter is also a space to highlight and emphasize the picture, known for debates surrounding the racial whitening of the Brazilian population, but similarly relevant in the study and approach to visualities. Among so many historicities, a nonlinear perspective of historical times is adopted, conduncing to explore the narratives that even go beyond the frames of the screen itself. Anchored in imagery culture, the dissertation is supported by theorists such as Aby Warburg, Jorge Coli, Michael Baxandall and Georges DidiHuberman.